Macroeconomic imbalances in the euro area: Where do we stand? - Beatrice Pierluigi; David Sondermann (European Central Bank (ECB), 2018)
This occasional paper reviews the macroeconomic developments in the euro area countries over the past 20 years. It analyses the accumulation of macroeconomic imbalances in the first decade of the EMU and their unwinding during the second decade. It shows that while flow imbalances have been corrected to a large extent, stock imbalances persist. The presence of large stock imbalances implies that the adjustment process needs to continue in the years to come. Accordingly, this paper reviews the national responses so far and the importance of well-functioning national economic structures for facilitating the adjustment process within the EMU. It shows that national structural policies are able to stimulate the supply side of the economy, increase adjustment capacity and mitigate the adverse growth effects of high debt and deleveraging. Finally, it gives an overview of the European response to address macroeconomic imbalances, i.e. the establishment of the Macroeconomic Imbalance Procedure (MIP). The MIP has contributed to increasing the general attention given to macroeconomic imbalances in the euro area and to the critical role that structural reforms play in facilitating their adjustment. Looking forward, further steps would appear to be warranted in order to move from greater awareness towards stronger ownership and implementation of reforms.
Keywords: E02; F45; O52; 330; Monetary Union; stock and flow imbalances; economic resilience; structural reforms; Macroeconomic Imbalance Procedure